The political roots of intermediated lobbying: evidence from Russian enterprises and business associations. (23rd February 2017) - Govorun, Andrei; Marques, Israel; Pyle, William
Abstract : A business enterprise interested in influencing the design, adoption or enforcement of a particular law, rule or regulation often confronts a choice. Does it lobby officials directly? Or does it do so indirectly, using a collective action group as an intermediary? We draw on data from a large, 2010 survey of enterprises across the Russian Federation to demonstrate that the propensity to engage in intermediated lobbying increases with region-level political competition. Our explanation builds on recent evidence confirming Mancur Olson's claim (1982) that less encompassing actors tend to lobby for more distortionary policies. We hypothesize that with greater political competition government officials become more responsive to encompassing voices (i.e. associations of businesses as opposed to single firms), since the electoral costs of being captured by narrower interests becomes greater. Evidence from a complementary survey of regional business association managers points in the same direction; the relative attention paid by officials to lobbying efforts by encompassing associations increases with political competition.